Screening of ginger varieties against rhizome rot disease complex in eastern ghat high land zone of Orissa - and SUGATA GHOSE, A.K. SENAPATI (Indian Phytopathology, 2005)
Ginger (Zingiber officinale) is one of the major spice crops of India as well as Orissa. In Orissa it is mainly grown in the hilly eastern ghat high land zone. Rhizome rot disease complex is an important production constraint. In the present study, 134 varieties of ginger were screened for three years at Potangi in Koraput district of Orissa against rhizome rot complex. Only one variety “ ZO – 16 “ was found to be resistant (percentage disease incidence, PDI, - 0.0 %), eight moderately resistant (PDI – 1.0 to 5.0 %), 19 tolerant (PDI – 6.0 to 15.0 %), 56 moderately tolerant (PDI – 16.0 to 25.0 %), 39 susceptible (PDI – 26.0 to 40.0 %) and 11 highly susceptible (PDI – above 40.0 %).